1965
DOI: 10.1111/j.1467-6494.1965.tb01370.x
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of muscular performance in hypnosis through exhortation and involving instructions1

Abstract: Earlier results which mdicated enhancement of performance in hypnosis over wakmg conditions have been brought mto senous question by a number of expenments, so that the issue is agam open For example, London and Fuhrer (1961), Slotnick and London (m press), and Levitt and Brady (1964) failed to find any superiority for performance in the hypnotic state over wakmg performance Slotmck and London found, however, that there was an mteraction between the hypnotic state and motivatmg mstructions, so that even thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1965
1965
1979
1979

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The evidence that alert hypnosis produced fewer errors in learnmg than standard hypnosis mdicates that the subjective differences reported by Ss following the arousmg instructions did in fact correspond to changes m their performance One possible conjecture is that the alert Ss could sustam attention better than the more passive ones The nobon that hypnosis IS always a state of alert attention has been refuted by recent studies, such as those of Amadeo and Shagass (1963) and Das (1964) A possible test of this conjecture is to consider as an mdicabon of mattenbon failure to respond m the three-second interval after presentmg an item Because the response items were enbrely familiar (the digits 1 through 8) there was no excuse for S's failmg to respond by a guess, even when he was unsure of himself In fact, he was instructed to guess If such failures to respond are taken as mdicators of inattention, we have the results m Table 4 Although the two groups of Ss gave the sdme number of blanks on the first (waking) session, the traditional hypnosis group increased the number of blanks (failures to respond) on the second day while the alert hypnosis group decreased their blanks, tbe differences between the two groups bemg bighly significant (p < 004) The conjecture is therefore supported that traditional hypnotic mducbons tend to reduce sustamed attenbon to leammg tasks, while alert hypnosis increases it. This findmg therefore has importance for any future studies comparing the effectiveness of hypnosis upon leammg or other performances requirmg sustamed attenbon Aldiough the differences between waking performance and alert hypnosis were not established in this mvesbgabon, it is believed that the results are mdetermmate at this point m view of the presence of one highly discordant S withm a group of five Ss m the wakmg-wakmg condition It wdl be recalled that m the earlier investigation (Slotnick et al, 1965) mvolved hypnosis was found superior to a wakmg condibon in a sustamed weightliftmg performance Another possibility is that for some Ss the relaxabon of badibonal hypnosis is more of a detriment to leamlng than the alert state is facilitating Only further study can decide between these possibilities…”
Section: Discxrssion and Summarymentioning
confidence: 75%
See 2 more Smart Citations
“…The evidence that alert hypnosis produced fewer errors in learnmg than standard hypnosis mdicates that the subjective differences reported by Ss following the arousmg instructions did in fact correspond to changes m their performance One possible conjecture is that the alert Ss could sustam attention better than the more passive ones The nobon that hypnosis IS always a state of alert attention has been refuted by recent studies, such as those of Amadeo and Shagass (1963) and Das (1964) A possible test of this conjecture is to consider as an mdicabon of mattenbon failure to respond m the three-second interval after presentmg an item Because the response items were enbrely familiar (the digits 1 through 8) there was no excuse for S's failmg to respond by a guess, even when he was unsure of himself In fact, he was instructed to guess If such failures to respond are taken as mdicators of inattention, we have the results m Table 4 Although the two groups of Ss gave the sdme number of blanks on the first (waking) session, the traditional hypnosis group increased the number of blanks (failures to respond) on the second day while the alert hypnosis group decreased their blanks, tbe differences between the two groups bemg bighly significant (p < 004) The conjecture is therefore supported that traditional hypnotic mducbons tend to reduce sustamed attenbon to leammg tasks, while alert hypnosis increases it. This findmg therefore has importance for any future studies comparing the effectiveness of hypnosis upon leammg or other performances requirmg sustamed attenbon Aldiough the differences between waking performance and alert hypnosis were not established in this mvesbgabon, it is believed that the results are mdetermmate at this point m view of the presence of one highly discordant S withm a group of five Ss m the wakmg-wakmg condition It wdl be recalled that m the earlier investigation (Slotnick et al, 1965) mvolved hypnosis was found superior to a wakmg condibon in a sustamed weightliftmg performance Another possibility is that for some Ss the relaxabon of badibonal hypnosis is more of a detriment to leamlng than the alert state is facilitating Only further study can decide between these possibilities…”
Section: Discxrssion and Summarymentioning
confidence: 75%
“…
The many studies which have compared performances of vanous kmds withm hypnosis with those within a nonhypnobc wakmg state have often failed to conbol S's mobvabon, on the supposibon that a hypnobzed S by virtue of the hypnotic state is highly mobvated to do what the hypnobst suggests to him In a previous mvestigabon from this laboratory (Slotnick, Liebert, & Hilgard, 1965) it was found that special "mvolving" mstructions, gomg beyond "exhortabon," led to enhanced performances by hypnotized Ss beyond their performances m the wakmg state or m the badibonal hypnotic state The present mvestigabon is concemed with the effect of mducmg a more alert hypnotic state withm hypnosis pnor to the undertaking of a leammg taskThe contradictory results of pnor expenmentabon designed to mvesbgate the lnffuence of hypnosis on leammg and recall may be understood m part on the basis of the failure to consider the mobvabonal or arousal state of S withm hypnosis Because it is difficult to untangle leammg and performance vanables, parbcularly m studies of acquisibon, the studies on f acilitabon of motor performance are also relevant In learmng studies, for example. Sears (1955) found some decrease m errors m the leammg of Morse code withm hypnosis as compared with a wakmg condibon, while Schulman and London (1963) found no significant improvement m the acquisibon of nonsense syllable pairs in hypnosis over that found in the wakmg state.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The S is striving to behave like a hypnotized person (Barber, 1965;Sarbin, 1950;White, 1941). Barber and Calverley (1963b;1964a), Levitt and Brady (1964), London and Fuhrer (1961), Orne (1959), Scharf and Zamansky (1963), and Slotnick, Liebert, and Hilgard (1965) have demonstrated that, if sufficient ingenuity is exercised in the special motivating techniques, Ss can jective, self -made ratings of hypnotic depth (O'Connell, 1964;Hilgard and Tart, 1966) indicated that the special instructions to imagine something as vividly as if it were really happening had the same effect as the induction of hypnosis. The lyrics used with the different groups were different, but the melody waa the same.…”
Section: Motivational Approaches To Hypnosismentioning
confidence: 99%
“…Although the effects of hypnosis and motivational instructions on motor endurance have received renewed attention in recent years (Orne, 1959 & London, 1965;and Slotnick, Liebert & Hilgard, 1965), no assessment of the effectiveness of these procedures on kinesthetic learning-the learning of complex motor sequences through kinesthetic feedback mechanisms-has been made. The closest approximations to such an assessment have involved coordinate-sense (visual-motor) learning such as digit symbol substitution, card sorting, and handwriting tasks.…”
Section: Introductionmentioning
confidence: 98%